Profiles of volatiles in microalgae depend on the extraction and analytical methods - de Carvalho, Carla C. C. R.; Neves, Kilian; de Almeida, Sebastião V. T. F.; Steinrücken, Pia; Kleinegris, Dorinde M. M. (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionThe incorporation of microalgae in food products is dependent on their volatile profiles, which significantly influence their organoleptic characteristics and, consequently, consumer acceptance. However, microalgae contain a myriad of volatile compounds, and their precise impact on olfactory and gustatory perception is not easily inferred. Nonetheless, volatiles imparting a fish-like odour are generally considered undesirable. To develop enzyme processes or other methods targeting malodour compounds, they must be identified and quantified in the microalgal biomass. However, no standard method allowing the extraction of all volatiles is available.MethodsIn the present study, the volatile profiles of the freshwater microalgal species Chlorella vulgaris and Arthrospira platensis and of the marine microalgal species Microchloropsis gaditana, Tetraselmis chui, and Phaeodactylum tricornutum were determined by gas chromatography.ResultsA total of five fractions were obtained by sequential elution of increasingly polar solvents and different methods to break the cells were tested. Additionally, the lipid composition of each species was determined and compared.DiscussionThe study clearly shows that extraction and analytical methods have a strong impact on the reported volatile and lipid profile of the cells.